Factors Affecting Gojek Drivers To Use Sharia Insurance In Surakarta - Pratama, Andira Putri; Nurohman, Yulfan Arif (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
This study examines the factors influencing Gojek drivers in Surakarta to use sharia life insurance. Despite adhering to Islamic principles and offering financial protection, participation among informal workers remains low. A quantitative descriptive method was employed, with data from 135 active drivers using purposive sampling. Variables analyzed include financial literacy, trust, income, premium rates, and service quality. SPSS was used for validity, reliability, classical assumption, and multiple regression tests. The results show that all five variables significantly influence decisions simultaneously. Partially, only financial literacy, premium rates, and service quality have a significant impact, while trust and income do not. The adjusted R² value of 0.560 indicates that the model explains 56% of decision variance. The study highlights the importance of financial literacy, affordable premiums, and quality service.